Applications of Non-Coding RNAs in Patients With Retinoblastoma - Fernandez-Diaz, Daniel; Rodriguez-Vidal, Cristina; Silva-Rodríguez, Paula; Paniagua, Laura; Blanco-Teijeiro, María José; Pardo, María; Piñeiro, Antonio; Bande, Manuel (Frontiers in Genetics, 2022)
Retinoblastoma (RB) is the most common primary intraocular malignancy in childhood. In the carcinogenic process of neoplasms such as RB, the role of non-coding RNAs (ncRNAs) has been widely demonstrated recently. In this review, we aim to provide a clinical overview of the current knowledge regarding ncRNAs in relation to RB. Although ncRNAs are now considered as potential diagnostic biomarkers, prognostic factors, and therapeutic targets, further studies will facilitate enhanced understanding of ncRNAs in RB physiopathology and define the roles ncRNAs can play in clinical practice.